(untitled) (Research, Society and Development, 2021)
Acetic fermentation or vinegar is the product obtained from fermented alcoholic wort, cereals or hydroalcoholic mixture with a minimum volatile acidity of 4g/100m.L-1. The present study produced, characterized and correlated the total dry extract with the density of the acetic fermented produced from the pineapple and apple peels. The fermentation process used pineapple and apple peel with culture medium, 10% hydroalcoholic solution, room temperature between 28 ± 2°C and irrigation 4 (four) times a day, without aeration for 12 days. Physico-chemical determinations of volatile acidity, density, dry extract, pH and alcohol content at 20°C were performed. The ANOVA variance analysis and the 5% Tukey test identified a difference between the analyzed acetic fermented. The acetic fermentations analyzed showed results within the established by Brazilian legislation. The relationship between the physical-chemical variables and the acetic fermented was studied by Principal Component Analysis (PCA). It was obtained that, with 5 components, more than 97.9% of the variability of the data were explained. There was a significant correlation between dry extract and vinegar density. The acetic fermented produced have similar physical-chemical characteristics to those produced industrially, which makes them suitable for consumption as commercial vinegars.